Application of MUSIC algorithm in real-world microwave imaging of unknown anomalies from scattering matrix. (15th May 2021) - Park, Won-Kwang
Highlights: We consider a real-time imaging of unknown anomalies from scattering matrix. We carefully explore the mathematical structure of MUSIC algorithm by finding relationships with the infinite series of Bessel functions of integer order. Explored theoretical result explains the reason for the unexplained phenomenon and unique determination. We present the experimental results using synthetic and real data to demonstrate the effectiveness of MUSIC. Abstract: In this contribution, we consider MUltiple SIgnal Classification (MUSIC)-type algorithm for a non-iterative microwave imaging of small and arbitrary shaped extended anomalies located in a homogeneous media from scattering matrix whose elements are scattering parameters measured at dipole antennas. In order to explain the feasibility of MUSIC in microwave imaging, we investigate mathematical structure of MUSIC by establishing a relationship with an infinite series of Bessel function of integer order and antennas setting. This is based on the representation formula of scattering parameters in the presence of small anomalies and the application of Born approximation. Simulation results using real-data at f = 925 MHz of angular frequency are exhibited to show the feasibility of designed algorithm and to support investigated structure of imaging function.